NT5E (CD73) as a prognostic biomarker and therapeutic target associated with immune infiltration in lung adenocarcinoma - Leyan Chen; Tuoya Qi; Bishu Zhang; Xuelong Wang; Mingfeng Zheng (Scientific Reports)
Abstract Lung adenocarcinoma (LUAD), the most common type of lung cancer, is a leading cause of cancer-related mortality. NT5E, an ecto-5’-nucleotidase enzyme, has been implicated in cancer progression, particularly in efferocytosis. Despite its potential involvement, the prognostic significance of NT5E and relationship with immune cell infiltration in LUAD have not been extensively explored. In this study, we performed a comprehensive analysis to elucidate the expression patterns of NT5E and its prognostic implications in LUAD using data from diverse public databases. Multiple computational algorithms, including CIBERSORT, ESTIMATE, and xCell, were employed to assess the correlation between NT5E expression and immune cell infiltration. We found that NT5E was significantly overexpressed at both the mRNA and protein levels in LUAD tissues. Elevated NT5E expression was significantly linked to multiple clinicopathological factors, including metastasis and pathological stage, and served as a strong predictor of poor prognosis in LUAD patients. Gene Set Enrichment Analysis (GSEA) indicated that NT5E plays a crucial role in regulating immune responses, as evidenced by differential gene expression associated with NT5E levels. A strong positive correlation was observed between NT5E expression and the presence of immune cells, including dendritic cells, macrophages, and CD4+ T cells, as well as the expression of various immune cell markers, suggesting that NT5E may influence the prognosis of LUAD patients by regulating immune cell infiltration. Additionally, drug sensitivity analysis highlights the potential of selumetinib and PD318088, both MEK1/2 inhibitors, to target NT5E in LUAD treatment, suggesting their use as single agents or in combination with other therapies. Collectively, these findings establish NT5E as a promising prognostic biomarker and therapeutic target in LUAD, particularly in the context of immune cell infiltration.